Out of the shadows of African traditional religion : Christ's deliverance of a sangoma - NTLA, Moss (Carlisle, Cumbria Hippo Books, 2017)
Francinah Baloyi was sixteen when the ancestors demanded that she continue the family tradition and be trained as a sangoma, one through whom the spirits would speak. She was twenty-three when Christ appeared to her in vision and cast out those spirits, showed her heaven and hell, brought her to repentance for her numerous abortions, and commissioned her to proclaim him. Today, she is a powerful preacher, who has led many to Christ. Her story demonstrates that conversion must affect every aspect of our life and challenges the syncretism that is threatening the church in Africa.
Keywords: Deliverance -- Africa